False positive results in the Widal test in adults immunized with the Commirnaty (Pfizer-BioNtech) and BBIBP-CorV (Sinopharm) vaccines against COVID-19 - Moya-Salazar, Jeel; Ciprian, Lizbeth Y.; Rojas-Zumaran, Víctor; Moya-Salazar, Belén; Goicochea-Palomino, Eliane A.; Contreras-Pulache, Hans (Frontiers in Medicine, 2025)
IntroductionVaccination against COVID-19 has generated a dramatic reduction in deaths and infections worldwide. However, there may be cross-reactivity with numerous biochemical and immunological markers. The Widal test for the detection of typhoid fever is an antigen–antibody test that can be affected by vaccination, causing errors in the results, so we determined the frequency of false positive results of the Widal test in adults vaccinated with Commirnaty (Pfizer -BioNtech) and BBIBP-CorV (Sinopharm) vaccines.MethodsWe conducted a cross-sectional study analyzing the titers of the serum agglutinins (S. typhi O and H antigen, and S. paratyphi A and B antigen) in 50 adults.ResultsThe proportion of false positives for O, H, A, and B antigens was 60, 44, 8, and 40%, respectively (total false positives = 38%). The Wildal tests’ results of patients with Commirnaty vaccine had higher false-positive dilution titers for O antigen [titer 1/400 (7.1%) and 1/800 (9.5%)] and H antigen [titer 1/400 (4.8%) and 1/800 (17.6%)]. We found differences in the paratyphic B by age and gender (p < 0.05).ConclusionOur results suggest misleading results of the Widal test in patients vaccinated against COVID-19, mainly in those vaccinated with Commirnaty. It is important to monitor and evaluate the results of routine immunological tests to ensure the quality of medical care.